Live wire eaudiobook Long-winded short stories. - Ripa, Kelly (HarperAudio, 2022)
An instant New York Times bestseller from Kelly Ripa—a sharp, funny, and honest collection of real-life stories showing the many dimensions and crackling wit of the beloved daytime talk show host. In Live Wire, her first book, Kelly shows what really makes her tick. As a professional, as a wife, as a daughter and as a mother, she brings a hard-earned wisdom and an eye for the absurdity of life to every minute of every day. It is her relatability in all of these roles that has earned her fans worldwide and millions of followers on social media. Whether recounting how she and Mark really met, the level of chauvinism she experienced on set, how Jersey Pride follows her wherever she goes, and many, many moments of utter mortification (whence she proves that you cannot, in fact, die of embarrassment) Kelly always tells it like it is. Ms. Ripa takes no prisoners. Surprising, at times savage, a little shameless and always with humor... Live Wire shows Kelly as she really is offscreen—a very wise woman who has something to say.